Tahlīl al-Akhtā’ al-Imlā’iyyah wa ‘Awāqibuha fi Ta’līm Mahārat al-Kitābah - Ardiyansyah; Danial Hilmi (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
Writing is one of the fundamental language skills; however, many students perceive it as one of the most challenging aspects of language learning, particularly in mastering imla’ (Arabic orthography). This study aims to identify and analyze the types of writing errors found in students' compositions, examine the factors contributing to these errors, and explore their implications for the teaching and learning of writing skills at Al-Nasyiin Al-Islami Islamic Boarding School, Pamekasan, Madura. This research employed a qualitative approach. Data were analyzed using the constant comparative method developed by Glaser and Strauss, which includes four stages: data reduction, data categorization, coding, and the formulation of working hypotheses. The findings reveal that students commonly made errors involving the addition and omission of letters, confusion between letters with similar pronunciations, substitution of letters or words, incorrect separation and connection of letters or words, improper writing of hamzah on alif, incorrect use of hamzah qatha’, and inaccurate placement of hamzah on waw. These writing errors were influenced by factors related to both students and teachers. Furthermore, the errors resulted in difficulties in constructing grammatically correct sentences, changes in the intended meaning of vocabulary, students’ inability to write complete and accurate sentences, and frequent violations of Arabic writing conventions. These findings suggest that teachers should systematically analyze students’ writing to identify recurring errors and develop effective instructional strategies that address students’ learning needs and improve their Arabic writing proficiency.